Fundamentals of Entrepreneurial Finance - Da Rin, Marco (Oxford University Press, Incorporated, 2020)
Entrepreneurial finance brings together the fast-moving world of entrepreneurship with the disciplined world of finance. Fundamentals of Entrepreneurial Finance provides an accessible, yet rigorous, framework for understanding how ambitious, high-growth start-ups can successfully obtain funding and interact with investors
Keywords: New business enterprises-Finance; Venture capital; Entrepreneurship; Risikokapital; Finanzierung; Electronic books; Aufsatzsammlung